Monitoring arts and psychomotor therapies: Further development and validation of the Self-expression and Emotion-Regulation in Arts and Psychomotor Therapies Scale (SERAPTS) - Suzanne Haeyen; Eric Noorthoorn; Evelien Joosten (PLoS ONE, 2025)
Background The present study is an extension of previous research, which resulted in the development of a valid, reliable and user-friendly tool for monitoring art therapy. The purpose of this study was to examine the extended reliability and sensitivity to change of the adapted version of the above scale, now called the Self-expression and Emotion Regulation in Arts and Psychomotor Therapies Scale (SERAPTS) for art, dance, drama, music and psychomotor therapy. Methods A pre-post design study was conducted on adult patients diagnosed with emotion regulation problems or personality disorder(s) cluster B/C. The study’s sample size was determined by the researchers to be 96 participants for the purpose of testing internal consistency, and 67 participants for the purpose of testing sensitivity for change. Results An excellent internal consistency was found for all domains of therapy combined (Cronbach’s α = 0.95). Additionally, high to excellent internal consistencies were identified for dance ( α = 0.88), drama ( α = 0.89), music ( α = 0.95), and psychomotor therapy ( α = 0.95), when considered separately. Furthermore, a significant sensitivity for change was identified within a 3-month timeframe (t = −4.39, p < .001), accompanied by a medium effect size (Cohen’s d = 0.54). Discussion The validity of the tool has been established in previous research. The present study sought to establish the applicability and reliability/sensitivity to change of the SERAPTS, with a view to extending it to the broad spectrum of all creative arts and psychomotor therapies. The SERAPTS was shown to be a valid and sensitive instrument for monitoring the effects of creative arts and psychomotor therapies, indicating healthy self-expression and emotion regulation skills that serve positive self-regulation.